Novel Single Nucleotide Polymorphisms (SNPs) and Genetic Features of the Prion Protein Gene (PRNP) in Quail (Coturnix japonica) - Kim, Yoonhee; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Prion diseases are fatal infectious diseases caused by conformational changes of a prion protein (PrPSc) derived from a normal prion protein (PrPC). Prion diseases have been reported in several mammalian hosts but not in any birds, including the most popular poultry species, of which chickens showed some resistance to experimental prion infection. To identify the genetic polymorphisms in the quail prion protein gene (PRNP), polymerase chain reaction and DNA sequencing were performed with gene-specific primers in 164 quails. Four in silico programs, including PROVEAN, PANTHER, SIFT, and AMYCO, were used to investigate the effect of non-synonymous single nucleotide polymorphisms (SNPs) on quail PrP. Furthermore, to investigate the genetic relationship of avian PrPs, phylogenetic analysis and multiple sequence alignments were performed using MEGA X program. Finally, the secondary and tertiary structures of avian PrPs were analyzed by SWISS-MODEL. We identified 33 novel SNPs in the quail PRNP gene, including three non-synonymous SNPs, c.56C>T (T19I), c.60C>T (V21I), and c.61G>A (A22S). Although V21I was predicted to have deleterious effects by SIFT, the substitutions of all three amino acids did not affect the amyloid propensity, 3D structure, or hydrogen bonds of quail PrP. Quail PrP showed a close evolutionary relationship and similar secondary and tertiary structures to chicken PrP compared to duck PrP. To our knowledge, this is the first report on the genetic and structural properties of the quail PRNP gene.